Graphene and its derivatives as biomedical materials: future prospects and challenges - Banerjee, Arghya Narayan (Interface focus, 2018)
Graphene and its derivatives possess some intriguing properties, which generates tremendous interests in various fields, including biomedicine. The biomedical applications of graphene-based nanomaterials have attracted great interests over the last decade, and several groups have started working on this field around the globe. Because of the excellent biocompatibility, solubility and selectivity, graphene and its derivatives have shown great potential as biosensing and bio-imaging materials. Also, due to some unique physico-chemical properties of graphene and its derivatives, such as large surface area, high purity, good bio-functionalizability, easy solubility, high drug loading capacity, capability of easy cell membrane penetration, etc., graphene-based nanomaterials become promising candidates for bio-delivery carriers. Besides, graphene and its derivatives have also shown interesting applications in the fields of cell-culture, cell-growth and tissue engineering. In this article, a comprehensive review on the applications of graphene and its derivatives as biomedical materials has been presented. The unique properties of graphene and its derivatives (such as graphene oxide, reduced graphene oxide, graphane, graphone, graphyne, graphdiyne, fluorographene and their doped versions) have been discussed, followed by discussions on the recent efforts on the applications of graphene and its derivatives in biosensing, bio-imaging, drug delivery and therapy, cell culture, tissue engineering and cell growth. Also, the challenges involved in the use of graphene and its derivatives as biomedical materials are discussed briefly, followed by the future perspectives of the use of graphene-based nanomaterials in bio-applications. The review will provide an outlook to the applications of graphene and its derivatives, and may open up new horizons to inspire broader interests across various disciplines.